PENGARUH KETERAMPILAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA KONVEKSI ISTANA MODE MADIUN - Wiwin Wiranti (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2016)
This  study aims to determine  tbe Employee   Skills in the Konveksi  Istana  Mode Madiun,  to determine  Employee  Productivity  in the Konveksi  Istana Mode Madiun,  as well as  to  determine   the  presence   or  absence   of  Vocational   Effect   on  Productivity   Among Employees   at the Konveksi  Istana  Mode  Madiun.  The  samples  in this  study  is purposive sampling   technique   that  all  employees   at  the  Konveksi   Istana   Mode   Madiun   part  of convection,   amounting  to 30 people.  Data  collection  using  questionnaires,   documentation and interviews.In    analyzing  the data using statistical  methods  Product  Moment,  To test this hypothesis   using the r test, F test and t test. The results  of the regression  analysis  ofY  = a +bX, the result Y = 11,737 + 0,757X,  to test that rcount  > r liable  (0.784  > 0.361),  or may be rejected  HO means  that there  is a skills  significant  relationship   with  work  productivity   of employee  at the Konveksi  Istana  Mode  Madiun.  Furthermore,   also obtained  results  which indicate that the F test ofF count >F table (44,5752::4.196)  or ::;;Sighit Sigprob  (0,000 ::;;0.05). Thus HO is rejected,  it means  there is an overall  effect of skills on labor productivity   at the Konveksi  Istana  Mode  Madiun.  In addition,  the t-test results  obtained  thit>  ttab  (6.676  > 2.048) or Sig hit < Sig prob (0.000 < 0.025) this situation  can be said to be no different  from the effect of employee  skills on work productivity  of employee  at the Konveksi  Istana Mode Madiun.